Karakteristik Kurma Tomat Ditinjau Dari Suhu Dan Lama Pengeringan - Anak Agung Hania Kusuma Handayani; I Gede Pasek Mangku; I Putu Candra (GEMA AGRO, 2021)
Tomatoes are one of the perishable vegetable commodities. One of the efforts to utilize tomatoes is to be processed into tomato dates. This tomato-based sweet is processed in such a way that it has a taste and shape like dates. There are several stages in the manufacture of tomato dates, one of which is the drying process. Temperature and drying time are important factors to produce the right product formulation in the manufacture of tomato dates. Drying with high temperatures will speed up the drying process, but can cause damage to the nutritional content. Drying at low temperatures will result in the drying process taking a longer time. This study aims to determine the effect of temperature and drying time on the characteristics of tomato dates and to determine the proper temperature and drying treatment in order to produce good characteristics of tomato dates. This research was conducted at the Laboratory of Processing and Basic Sciences, Faculty of Agriculture, Warmadewa University. This study is a factorial experimental study with a Randomized Block Design (RBD) consisting of two factors. Factor I (drying temperature): K1(70ËšC) and K2 (80ËšC). Factor II (drying time): S1 (12 Hours), S2 (16 Hours), S3 (18 Hours), S4 (24 Hours ). Variables observed on tomato dates were color analysis, browning intensity, acidity, moisture content, vitamin C, antioxidant activity, reducing sugar content, texture, and sensory characteristics. The results showed that the treatment at a drying temperature of 80ËšC for 16 hours produced tomato dates with the best characteristics with an average rating of 5.33 (slightly like), taste 5.60 (like), texture 5.33(slightly like), color 5.60 (like), overall acceptance 5.60 (like), brightness level (L*) 20.03, redness level (a*) 40.39, yellowness level (b*) 8.23, browning intensity 23.26, acidity degree (pH) 4.40, water content 27.80%, vitamin C 3.75 mg/100gr, antioxidant activity 22.95%, reducing sugar content 71.28 mg/100gr, texture 3.50 kg/cm2, yield 26.50%.